Is anybody there ? - Ure, Jean. (London : Harper Collins, 2004)
"Joanna, Chloe and Dee are the best of friends. They may be seen as outsiders at school, but they're an inseparable trio. Joanna lives with her mom. But Mom's not your normal, average parent-she's a medium. Cool, you might think, but Jo's inherited her mother's psychic ability, which is not really compatible with school life! When one of their classmates goes missing, Chloe and Dee persuade Jo to use her gift to find her-but having a gift is one thing, dealing with the consequences is another."--Publisher.
5-8.
Keywords: Missing children -- Fiction; Missing children -- Juvenile fiction; Psychic ability -- Fiction; Psychic ability -- Juvenile fiction